PENERAPAN ASAS PACTA SUNT SERVANDA DALAM PENYELESAIAN PERJANJIAN PINJAM MEMINJAM DI KOPERASI SWASTI SARI - Baud, Gilbert Leonard; Aloysius, Sukardan; Jacob, Yossie M Y (Petitum Law Journal, 2024)
Pacta sunt servanda principle has several implications for compliance with agreements, repayment of obligations, legal protection, invalidity of this principle, negotiation and renegotiation. Based on this case, formulated the main problems: (1) How is the application of Pacta sunt servanda principle in the settlement of lending and borrowing agreements in Kupang Kota branch of Swasti Sari Cooperative? (2) What are the efforts to resolve violations of the borrower's loan agreement made by Koperasi Swasti Sari Kupang Kota Branch? This study is empirical juridical research. The results showed that Saving adn Loan Cooperative Kopdit Swasti Sari as the creditor applies the principle of Pacta sunt servanda, in this case as a creditor, of course, does not ignore or violate the agreement, because the consequences can harm the creditor itself. The procedure for resolving defaults in credit agreements at Saving adn Loan Cooperative Kopdit Swasti Sari is divided by borrower categories if the debtor has income and there is good faith to complete the loan, Rescheduling can be carried out, if the debtor (cooperative member) has income but there is no good faith to complete the loan, seizure of collateral/collateral items can be carried out.